Itolizumab regulates activating and inhibitory signals on effector cells, improving their cytotoxicity against CD318+ tumor cell lines - González Muñoz, Cynthia; Álvarez Arzola, Rydell; Calvo Pérez, Adanays; Frometa Campanón, Milagro de la Caridad; Hernández Casaña, Patricia; Fernández-Calienes Valdés, Aymé; Lorenzo-Luaces, Patricia; Mazorra Herrera, Zaima; Crombet Ramos, Tania; Labrada Mon, Mayrel (Frontiers in Immunology, 2025)
IntroductionThe CD6‐CD318 axis has emerged as a potential target for immuno‐oncology. Recent work has shown that blocking the CD6‐CD318 interaction with a murine anti‐human CD6 antibody increases lymphocyte cytotoxicity. However, several studies have demonstrated the drawbacks associated with the clinical use of murine antibodies and the variability among anti‐CD6 antibodies. Therefore, evidence that the first‐in‐class humanized anti‐human CD6 antibody itolizumab could be used for cancer immunotherapy may be a breakthrough in developing an antitumor clinical approach.MethodsPhenotypic and functional characterization of peripheral blood mononuclear cells (PBMCs) from healthy donors after challenge with CD318+ cell lines was performed by flow cytometry. In addition, IFNγ was determined by ELISA in culture supernatants. Immunohistochemical analyses of breast tumor samples were also performed.Results and DiscussionHere, we provide evidence supporting the rationale for itolizumab in cancer immunotherapy. The blockade of the CD6-CD318 interaction by itolizumab increases the cytotoxic capacity of CD8 T and NK cells over CD318+ tumor lines, reverses the NKG2A/NKG2D ratio, and increases granzyme B and IFNγ production. Itolizumab also regulates immune responses by downregulating CD5 expression and upregulating PD-1 and CTLA-4 inhibitory receptors on lymphocytes, which contribute to reducing exacerbated responses and additively enhancing CD318+ tumor cell cytotoxicity when combined with other immunocheckpoint inhibitors. In addition, we report that CD6‐CD318 interaction inhibits lymphocyte proliferation and survival while downregulating CD6 expression on lymphocytes in vitro and in human breast cancer tissue samples, reinforcing the role of the CD6‐CD318 axis as an immune checkpoint and highlighting the potential of itolizumab as an immune checkpoint inhibitor. Taken together, our results provide the first evidence linking the blocking of the CD6-CD318 axis by itolizumab with the potentiation of functional properties of lymphocytes, highlighting itolizumab as a novel promising immunotherapy for CD318+ tumors and supporting the relevance of new combinatorial therapies with checkpoint inhibitors.